Mengunyah Permen Karet Terhadap Post-Operative Nausea And Vomiting (Ponv) Pada Sectio Caesarea - Shindy Gustarina; Anggra Trisna Anjani; Yance Komela Sari; Nopan Saputra; Milya Novera; Astilia (Jurnal Amanah Kesehatan, 2024)
Caesarean section surgery with spinal anesthesia techniques has an unpleasant post-operative effect, including nausea and vomiting called post-Operative Nausea & Vomiting. (PONV). To prevent other PONV alternatives used with non-pharmacological therapy by chewing rubber candy. The purpose of the study is known to have a link between chewing gum and the occurrence of PONV in Caesarean section patients. Cross sectional research design with a total sample of 34 respondents. Method of non probability sampling using consecutive samplings. PONV assessment can use the observation sheet. Using the Chi-Square test. The results of the study showed that there was a connection between chewing rubber candy and the occurrence of PONV in caesarean section patients with a p (value) of 0,000. It is hoped that further research will be conducted to examine blood sugar levels before and after chewing gum for changes in blood sugar that may affect the assessment of PONV especially in patients with Diabetes mellitus